2020
DOI: 10.3389/fpsyg.2020.01853
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Entrepreneur’s Psychological Capital on Employee’s Innovation Behavior Under Leader-Member Exchange Relationship

Abstract: How to make use of leaders' psychological capital to improve the innovation behavior of employees has become an important issue for the talent management of enterprises today, and it is also the goal that enterprises must pursue if they want to stand out in fierce competition. Therefore, a total of 154 enterprises in a high-tech area were selected for questionnaire survey in this study. The correlation between leadermember exchange (LMX) relationship (emotion, loyalty, contribution, and professional respect), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…The cross-level sociodemographic dissimilarity between chairs and their teams due to social categorization will affect the interaction between chairs and their teams. It will also destroy the construction of good psychological state and interpersonal relationship between leaders and their teams and impede the process of innovative strategic decision-making ( Li T. et al, 2020 ). The similarity-attraction paradigm can also explain the negative effect of the chair–team sociodemographic dissimilarity from another perspective.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The cross-level sociodemographic dissimilarity between chairs and their teams due to social categorization will affect the interaction between chairs and their teams. It will also destroy the construction of good psychological state and interpersonal relationship between leaders and their teams and impede the process of innovative strategic decision-making ( Li T. et al, 2020 ). The similarity-attraction paradigm can also explain the negative effect of the chair–team sociodemographic dissimilarity from another perspective.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…It can provide new products and improve service processes ( Enz and Siguaw, 2003 ; Orfila-Sintes and Mattsson, 2009 ; Su, 2011 ), and influence the competitive advantage and performance of hotels ( Ottenbacher, 2007 ; Pivčević and Petrić, 2011 ). A significant number of studies have tried to find the influencing factors for these positive consequences ( Chang et al, 2011 ; Tu and Lu, 2013 ; Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that the innovation ability of employees is influenced by their leaders ( Zubair et al, 2015 ; Liu et al, 2017 ; Harbi et al, 2019 ; Su et al, 2019 ), and research on how to improve employee innovation by leader psychological capital is growing ( Mohamad et al, 2019 ). However, knowledge on the level of leader psychological capital affected employees’ innovative behavior remains ambiguous ( Li et al, 2020 ). Therefore, this study explored the effect of leader PsyCap on innovative behavior in employees.…”
Section: Introductionmentioning
confidence: 99%
“…Employee innovation plays a key role in providing continuous competitive advantage to the organization (Ghosh, 2010;Turró et al, 2014;Odoardi et al, 2015;Shin et al, 2017). Many literature concern with employee innovation, and these reviews identified that employee psychological capital has a positive effect on employee innovation (Liang and Li, 2016;Fang et al, 2019;Tang et al, 2019;Tsegaye et al, 2020), but few of these studies focus on the relationship between leader psychological capital and employee innovation (Peterson et al, 2009;Li et al, 2020). Positive psychology posits that leader psychological capital (PsyCap) is a positive psychological resource.…”
Section: Introductionmentioning
confidence: 99%